2001
DOI: 10.1002/1529-0131(200104)44:4<856::aid-anr142>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of dendritic cells in systemic lupus erythematosus: Phenotypic and functional deficiencies

Abstract: Objective Systemic lupus erythematosus (SLE) is a systemic autoimmune disease characterized by B cell hyperactivity and defective T cell functions, including interleukin‐2 production and proliferation. The defects in T cell function may result from underlying defects in antigen‐presenting cell (APC) function. The present study was undertaken to investigate phenotypic and functional characteristics of peripheral blood dendritic cells (DC), as the most potent APC, in SLE patients in comparison with healthy contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(44 citation statements)
references
References 43 publications
4
37
3
Order By: Relevance
“…*Statistically significant differences were considered when P \ 0.05 (Mann-Whitney U test) (Table 1). Indeed, our results were in agreement with previous reports demonstrating a lower number of peripheral DCs in SLE patients when compared with healthy subjects [32][33][34] but disagreed with others reporting significant alterations in the proportion of circulating mDCs/ pDC subtypes [35]. Those apparent discrepancies in the relative distribution of different peripheral DC subpopulations are probably due to the fact that in other works, they did not include a DC subpopulation, defined by us as CD14 -/low CD16 ?…”
Section: Discussionsupporting
confidence: 76%
“…*Statistically significant differences were considered when P \ 0.05 (Mann-Whitney U test) (Table 1). Indeed, our results were in agreement with previous reports demonstrating a lower number of peripheral DCs in SLE patients when compared with healthy subjects [32][33][34] but disagreed with others reporting significant alterations in the proportion of circulating mDCs/ pDC subtypes [35]. Those apparent discrepancies in the relative distribution of different peripheral DC subpopulations are probably due to the fact that in other works, they did not include a DC subpopulation, defined by us as CD14 -/low CD16 ?…”
Section: Discussionsupporting
confidence: 76%
“…It was suggested that patients with SLE have increased differentiation of precursor cells into monocyte-derived DC due to the effect of IFN-a produced by pDC [13]. Myeloid DC were found to be either spontaneously hypo- [14,15] or hyperactivated [16,17] with a decreased [14,15] or increased [17] mixed lymphocyte reaction (MLR). However, their capacity and function following apoptotic cell interaction was not examined.…”
Section: Introductionmentioning
confidence: 69%
“…The effects of previous influenza vaccinations or natural infections could not be completely excluded. Whether intrinsic defects are involved, such as a defective antigen-presenting cell function (32,33), is uncertain.…”
Section: Discussionmentioning
confidence: 99%